Hardware Implementation and Design of PV Off-Grid for smart Street Lighting System - Singh, Satwinder (My University, 2014)
Street light is a raised source of light that is commonly used along walkways and streets when the surrounding turns dark. By using the latest technology light emitting diode, the control of light intensity is possible by using sensors which can detect the movement of vehicles. As the vehicles move forward, the light intensity goes on increasing for a few seconds and as it passes away the intensity decreases. LED lamps have several advantages .For a fixed input power it provides more lumen and less Co2 compared to conventional lamps like CFL, Fluorescent, tungsten etc. By using the auto switching system, we can also control power consumptions at the streets and eliminating manpower. The production and use of photovoltaic cell to generate electricity are an increasingly popular resource solution globally. The focus of proposed work is to make the most efficient use of the energy received from the sun to power street lights. Solar energy is collected with the aid of solar panel and battery is charged during day time and this energy is used for power street lights during night. In addition, if a solar tracker system is used we can attain maximum energy from the sun.
M.E. (Power Systems)
Keywords: LED; HPS; CRI; Smart street lighting system; light intensity control